Determinants of Successful Economic Independence in Pesantren: SEM Analysis - Adamin, Muhammad; Firdaus, Achmad; Ali, Zulkarnain Muhammad (SMART Insight, 2024)
This study analyzes the factors that influence the economic independence of pesantren with a focus on the role of leaders, business units, and santri empowerment programs. Using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, data were obtained from 104 respondents who are boarding school administrators. The findings show that pesantren leaders have a significant positive effect, which is reflected in involvement in ulama organizations and community participation. Business units, through the management of kopontren, as well as the empowerment of santri with the integration of entrepreneurship in the curriculum, also contribute to the success of economic independence. Recommendations for the development of pesantren economic independence include utilizing internal potential, developing an entrepreneurial spirit among santri, and utilizing alumni networks. Future research is recommended to expand the scope of respondents and consider additional variables for a more comprehensive analysis.This study analyzes the factors that influence the economic independence of pesantren with a focus on the role of leaders, business units, and santri empowerment programs. Using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, data were obtained from 104 respondents who are boarding school administrators. The findings show that pesantren leaders have a significant positive effect, which is reflected in involvement in ulama organizations and community participation. Business units, through the management of kopontren, as well as the empowerment of santri with the integration of entrepreneurship in the curriculum, also contribute to the success of economic independence. Recommendations for the development of pesantren economic independence include utilizing internal potential, developing an entrepreneurial spirit among santri, and utilizing alumni networks. Future research is recommended to expand the scope of respondents and consider additional variables for a more comprehensive analysis.